Implementation of Web Cam as Motion Detector with DirectShow Interfacing - Santoso, Yonatan; Setiyawan, Iwan; Papilaya, Victor N. (Makara Journal of Technology, 2009)
Implementation of Web Cam as Motion Detector with DirectShow Interfacing. One of many ways to take control a web cam is by using DirectShow which is integrated in DirectX. DirectShow acts like an API therefore it is easier to use. Afterwards, web cam will be implemented to detect object’s motion as well as camera surveillance. The method is by comparing a reference image with other image which is taken lately. If there are differences between those image it means motion has been detected.